-2(-k+1)=-2(k-5)

Simple and best practice solution for -2(-k+1)=-2(k-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(-k+1)=-2(k-5) equation:


-2(-k+1)=-2(k-5)

We simplify the equation to the form, which is simple to understand
-2(-k+1)=-2(k-5)

Reorder the terms in parentheses
+(+2k-2)=-2*(k-5)

Remove unnecessary parentheses
+2k-2=-2+*(+k-5+)

Reorder the terms in parentheses
+2k-2=+(-2k+10)

Remove unnecessary parentheses
+2k-2=-2k+10

We move all terms containing k to the left and all other terms to the right.
+2k+2k=+10+2

We simplify left and right side of the equation.
+4k=+12

We divide both sides of the equation by 4 to get k.
k=3

See similar equations:

| n+7-n=4 | | 4m-n=m | | 4p^3-9p=0 | | 3-5(3x-11)=3x+7 | | 3x+3+5x=-13 | | 55=-4r-9 | | -2(x+10)=3(2x-4) | | 15y-12(-26.75+1.25y)=321 | | 2(x+7)=x+5 | | 48u^2-70u+25=0 | | (6x+7)(2x-1)= | | 8(11-x)=15 | | 5x+3=-5+2x+20 | | 8u^2+43u-30=0 | | t(t+3)=70 | | 3(8x-2x)+21-x=7x | | 6(1-3m)+4=-6-2(-4+5m) | | 6(x-2.5)/=8-6(3.5+x) | | (6x+7)(1+-2x)= | | 6u^2+31u-30=0 | | 0=2x^2-9x+4 | | -14=c | | 4rcos+rsen=8 | | 8+a=13 | | 4x^2+2x-110=0 | | 9x-3=6x | | 9+8(x+2)= | | 6u^2-53u+40=0 | | (6x+7)(1+2x)= | | X^2-16X+64=y | | 2+(2-6)-2=10 | | -(2.1c-4d)= |

Equations solver categories